Praktik Akuntansi Sederhana Peternak Cacing : Sebuah Studi Fenomenologi di Desa Cabean Kabupaten Madiun Provinsi Jawa Timur - Nawangsari, Ajeng Tita; Cahyanti, Kharisma Galuh; Junjunan, Mochammad Ilyas (Akuntansi: Jurnal Akuntansi Integratif, 2022)
This study aims to answer the question of how simple accounting practices for worm farmers are based on the meaning of accounting for worm farmers. The research method used in this research is multiparadigm research with interpretive as the paradigm. The analysis tool uses transcendental phenomenology with data collection through interviews, observation and documentation. Then the data were analyzed using a set of transcendental phenomenological methods. Among others, analyzing noema, epoche, noesis, intentional analysis, eidetic reduction and finally discussing the results of the interview data. The results of this study are the accounting practices of worm breeders based on the meaning of accounting understood by the informants. The result of this interpretation is "a practice of managing finances by memory or simple recording". Accounting is interpreted as such in accordance with the experience and awareness of worm breeders in running their business. Such meaning outputs to the accounting practices carried out by each informant. The practice referred to here is the practice of recording, measuring costs and also determining profits.